Reflection on: “The Circulation of Evaluative Information” - Nyholm, Inga (Scandinavian Journal of Public Administration, 2021)
In this text I will focus on evaluation and evaluative information in a rapidly changing environment, as well as evaluation as a process determined by multiple and sometimes even hidden choices. “Evaluation has become such a widespread social phenomenon that the term ‘The Evaluation Society’ is often referred to. This is a society with flows of evaluative information.” This quote from the article “The Circulation of Evaluative Information” (hereafter: the article) illustrates that today evaluative information, the number of evaluations performed, is increasing steadily, at the same time as types and levels of evaluation are becoming more and more diversified.